Study on Consumption of Chicken Eggs in Hyderabad District - Memon, A.; Memon, A.S.; Soomro, A.H.; Rajput, N.; Leghari, I.H.; Moriyani, A.A.; Ansari, N.N. (Pakistan Journal of Nutrition, 2009)
A survey based study on consumption of chicken eggs in house holds of Hyderabad district was carried out on pre-tested questionnaire during 2006-2007. For this purpose, 200 consumers were selected for interview and mostly were educated, married and having monthly income in the range of 1000-10000 rupees. According to the majority of religious groups, 86% representation was to Muslims and 14% to Hindu consumers. Among consumers, 40% were public sector employees, while 60% were from the private sector business. Majority of the consumers liked commercial eggs and their perception on nutritive value was partial. A weaker frequency of purchase was distinguished. Majority of consumers (51%) purchased and consumed eggs daily . Most of the consumers prefer commercial eggs over desi eggs. Omelet was the most preferred item after cooked by wives of the consumers. The eggs were more frequently consumed in winter season as compared to other seasons. The purchasing capacity of egg consumers was very weak and 73% consumers could purchase 1-3 eggs. Within family disliking of poultry was also observed. However, high frequency (71%) preferred to eat whole egg rather to take yolk or white. Eggs were the preferred item at breakfast over other food items. In case of disease outbreak in chicken, 54% consumers eat eggs and also 57% consumers use eggs when increased price in the market. Consumers also sacrify egg in disease condition as old myth.